Mycorrhizal inoculation impact on Acorus calamus L. - An ethnomedicinal plant of western Himalaya and its in silico studies for anti-inflammatory potential - Verma, Rachna; Kumar, Dinesh; Nagraik, Rupak; Sharma, Avinash; Tapwal, Ashwani; Puri, Sunil; Kumar, Harsh; Kumari, Amita; Nepovimova, Eugenie; Kuca, Kamil (Journal of ethnopharmacology, 2021)
ETHNOPHARMACOLOGICAL RELEVANCE: Different plants are used for the treatment of various ailments and Acorus calamus L. is one such plant found in Western Himalaya. Rhizome of this plants has ethnomedicinal significance, as its rhizome is used for curing fever, pain and inflammation. An attempt has been made to alter the phytochemicals and increase its antioxidant property in a sustainable way with the help of mycorrhizal inoculation. AIM OF THE STUDY: Study of mycorrhizal (Funneliformis mosseae) impact on the biological activities and phytochemical profile of A. calamus L. rhizome and in silico studies of phytochemicals for their anti-inflammatory property. MATERIALS AND METHODS: F. mosseae was mass multiplied by single spore culture and then A. calamus rhizomes were inoculated with it. Antioxidant potential of rhizome extract was observed by DPPH and FRAP assays and the phytochemical profiling was done with GC-MS analysis. For observing antimicrobial activity disc diffusion method was employed. Dominant phytochemicals α-asarone and monolinolein TMS were chosen for molecular docking studies against four receptors (4COX, 2AZ5, 5I1B, 1ALU). RESULTS: There was increase in antioxidant activity of rhizome extract after mycorrhizal inoculation. However, no change in antimicrobial activity was observed in the plant after mycorrhizal inoculation. The comparison in phytochemicals was observed by GC-MS analysis which showed qualitative and quantitative variation in biochemical content in plants. The phytochemical, α-asarone and monolinolein TMS showed highest docking score and least binding energy against 1ALU and 4COX respectively for anti-inflammatory activity. CONCLUSION: Medicinal plants are potential source of antioxidants which can be increased by mycorrhizal inoculation without addition of chemical fertilizers and also results in altering the phytochemical composition.
Keywords: antiflogistika; Antimicrobial activity; fytonutrienty; Antioxidants; houby; GC-MS analysis; počítačová simulace; simulace molekulového dockingu; rostlinné extrakty; India; Rhizome; Western himalaya; antiinfekční látky; oddenek; Anti-Infective Agents; Antioxidant potential; mykorhiza; Computer Simulation; tradiční lékařství; Fungi; Mycorrhizae; AMF; plynová chromatografie s hmotnostně spektrometrickou detekcí; Anti-Inflammatory Agents; antioxidancia; Acorus; Plant Extracts; diskové difúzní antimikrobiální testy; Gas Chromatography-Mass Spectrometry; puškvorec; Phytochemicals; Medicine, Traditional; Indie; Molecular Docking Simulation; Disk Diffusion Antimicrobial Tests